2018
DOI: 10.1089/tmj.2017.0210
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Parkinson's Disease: Limited Engagement Between Local Clinicians and Remote Specialists

Abstract: The greatest perceived barrier among respondents was distance from patient to specialist, and 40% of local clinicians would recommend video visits. As telemedicine grows, improved communication between remote specialists and local clinicians is likely needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In our study, all the patients included completed satisfactorily the online evaluation. Elson et al reported that the greatest perceived barrier for patients with PD was distance from patient to specialist. Moreover, 40% of local clinicians would recommend video visits to facilitate communication between remote specialists and local clinicians .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all the patients included completed satisfactorily the online evaluation. Elson et al reported that the greatest perceived barrier for patients with PD was distance from patient to specialist. Moreover, 40% of local clinicians would recommend video visits to facilitate communication between remote specialists and local clinicians .…”
Section: Discussionmentioning
confidence: 99%
“…Elson et al reported that the greatest perceived barrier for patients with PD was distance from patient to specialist. Moreover, 40% of local clinicians would recommend video visits to facilitate communication between remote specialists and local clinicians . A high interrater reliability was found for all online measurements carried out in this study (ρ = 0.769‐1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tele-neurology can exist as a local hub or facility that is connected electronically to a larger hospital, neurologist, or specialist to provide consultation. The audio-visual conferencing equipment often consists of a camera with pan, tilt, and zoom capabilities so that the neurologist or specialist can examine and speak to the patient [11]. Other sorts of devices used to evaluate patients remotely include using robotic telepresence (RTP) in which a robotic audiovisual platform can move around to create a sense of “being present” at the remote site [12].…”
Section: Reviewmentioning
confidence: 99%
“…Despite the barriers some patients face in accessing traditional face-to-face neurology care such as traveling large distances or having a disability, in a survey of local physicians of Parkinson’s patients, many were ambivalent about recommending tele-health visits for their patients. Many also reported not receiving recommendations of care from the tele-neurologist, but of those who did, they implemented some or all of their recommendations and found them to be beneficial [11]. Despite this, tele-neurology is still growing; in a survey to neurology departments around the United States, tele-neurology is being applied, by way of consultations, for acute stroke, movement disorders, neurocritical care, and chronic care [27].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation